Importance of Student Consultant Program about Education and Career Counselling In Junior and Senior Colleges - Patel Vidhi Pinal (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
When it comes to selecting a major, learning about various career fields, and finding internships and jobs, college career centres are an invaluable resource. To satisfy the demands of recruiters and students, career centres must offer a more complex range of virtual and one-on-one services. To meet students’ requirements holistically, the career services office must work in conjunction with other departments, such as the college counselling centre. Making the right academic and professional choices is a common challenge for students in a fast-paced, cutthroat educational setting. In order to help junior and senior college students make well-informed decisions about their education and future careers, Student Consultant Programs have become essential support networks. The importance of SCPs at educational institutions is examined in this research, with a focus on how they contribute to employability improvement, career orientation, academic planning, and psychological support. This study emphasizes the beneficial effects and potential future applications of student consultant programs in influencing student achievement through qualitative analysis and institutional case studies.